Attitude, Perceived Behavioral Control, Organizational Commitment and Intention to Whistleblowing: The Moderating of Religiosity - Fitriani Saragih; Dahrani Dahrani; Pandapotan Ritonga; Tasya Amara; Vira Novira Liza (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose – This study aims to determine the factors that most influence the Determinant Model of Intention to Whistleblowing with Religiosity as a Moderating Variable: Survey of State Civil Apparatus in The Government of Medan.Methodology – The research approach used in this research is to use an associative approach. The location of this research is Medan, and the subject is the State Civil Apparatus in the Government of Medan. The population of this study was all state civil apparatuses in the government of Medan. This study looked for suitable respondents who have shopped at minimarkets more than once. The sampling technique used is non-probability (non-probability), more precisely, purposive sampling. This study uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS), an alternative model estimation method, to answer the problem formulation.Findings – Based on the analysis that has been done, the results show that attitudes, perceptions of control, and organizational commitment affect the intention to do whistleblowing, and religiosity can moderate the influence of attitudes, perceptions of behavioral control, and organizational commitment on the intention to do whistleblowing.Originality/Novelty – The study model includes five variables and uses the notion of moderation by employing SEM-PLS to evaluate each connection in the model.